2010
DOI: 10.2460/ajvr.71.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unfocused extracorporeal shock wave therapy on healing of wounds of the distal portion of the forelimb in horses

Abstract: Treatment with ESWT did not accelerate healing of equine distal limb wounds, but treated wounds had less exuberant granulation tissue and appeared healthier than controls. Therefore, ESWT may be useful to prevent exuberant granulation tissue formation and chronic inflammation of such wounds, but further studies are necessary before recommending ESWT for clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Unfortunately, these complications are frequent outcomes after skin wounding on the limb and may adversely affect function, often through lameness . For this reason, Theoret et al developed a standardized experimental model of equine EGT, which has since been used in several studies to investigate the causes and possible cures of the condition …”
mentioning
confidence: 99%
“…Unfortunately, these complications are frequent outcomes after skin wounding on the limb and may adversely affect function, often through lameness . For this reason, Theoret et al developed a standardized experimental model of equine EGT, which has since been used in several studies to investigate the causes and possible cures of the condition …”
mentioning
confidence: 99%
“…48 This analgesic effect is discussed in a study describing a decrease in weight-bearing asymmetry after ESWT of horses with proximal suspensory ligament desmitis, however, there was no change in skin sensitivity after treatment. 41 A study showed a positive effect on wound healing time, but not any significant changes in histology or immunohistochemical analyzes 49 , nor difference in area of epithelialization and percentage of wound contraction. Further, studies have investigated the effect on bone healing.…”
Section: Outcome Measuresmentioning
confidence: 98%
“…It stimulates physiological angiogenesis, due to the release of NO and vascular growth factors at the site of the ulcer. Previous studies [15,[19][20][21][22][23][24][25][26] showed that shock waves are effective in stimulating several endogenous growth factors such as EGF, IGFl, VEGF and nitric oxide production, inducing angiogenesis and promoting the healing of fractures, ulcers and complex lesions. Gerdesmeyer et al [27] showed in their studies the antibacterial effect of shock waves mediated by cavitation.…”
Section: Discussionmentioning
confidence: 99%